FEM: Mono-implant cement retained crown with two different adhesive materials - Shakir, Shahad M; Muhsin, Saja A; Al Marza, Raad S (Journal of Baghdad College of Dentistry, 2023)
Background: The finite element method (FEM) is expected to be one of the most effective computational tools for measuring the stress on implant-supported restorations. This study was designed using the 3D-FEM to evaluate the effect of two adhesive luting types of cement on the occlusal stress and deformation of a hybrid crown cemented to a mono-implant. Materials and Method: The mono-screw STL file was imported into the CAD/CAM system library from a database supported by De-Tech Implant Technology. This was to assist in the accurate reproduction of details and design of a simulated implant abutment. Virtually, a digital crown was designed to be cemented on an abutment screw. A minimum occlusal thickness of 1mm and marginal fitting of 1.2mm was intended. An 80µm cement interface thickness for this study’s purposes was applied using U-Cem Premium and 3M RelyXTm adhesives. The FEA software meshed into tetrahedral elements. Two three-dimensional finite element models were simulated under different loads of 200N, 400N, 600N, 800N, 1000N, 1200N, and 1400N. Results: The results showed that the hybrid ceramic crown attached to a mono-implant with each adhesive cement exhibited comparable stress and strain. However, the amount of distortion was less when RelyX cement was used. Conclusion: Overall, it was advisable to use 3M RelyXTm adhesive cement up to 1400N load.